Partisipasi Masyarakat Lokal Dalam Pengembangan Pariwisata Di Desa Jatiluwih, Kabupaten Tabanan, Bali - Wardana, I Gusti Agung Fajar Wisnu; Adikampana, I Made (JURNAL DESTINASI PARIWISATA, 2018)
Tourism development should involve the local community as one of strakeholders in its management. In the management of tourist villages, local community should be active in tourism activities to gain the benefits . Therefore local communities also have the right to be able to earn the economic benefits equitably. This study aims to determine the participation of local communities in the management of tourism activites in the Jatiluwih Village, Bali. This research is important because local community participation in tourist village can determine sustainable development       The research methodology used in this study is a qualitative research, with observation, semi-structured interviews, and documentation as well as using the concept of a tourism village and community participation theory to analyze the problems in the field.       The result shows that decision-making in local community participation is still lacking. They have chance to listened or hearded but their opinion not necesseraliy considered.  Benefits received by the local community from tourism activities are the community has begun to get the right share from the tourism  development of their village.   Keywords : Community  Participation, Tourism Development, Jatiluwih Village